Kualitas dan Efisiensi Serapan N pada Centrosema pubescens (centro) dan Pueraria phaseoloides (puero) Akibat Pemberian Pupuk Iodine - Adriani Darmawati; Syaiful Anwar; Irwan Hermanan (Agricultural Faculty, 2015)
(The quality and absorption efficiency of N at Centrosema pubescens (centro) and Pueraria phaseoloides (puero) cause add of iodine fertilizer)ABSTRACT. The aimed of the experiment was to know the effect of iodine fertilizer when applied to the soil on the quality and the efficiency of Nitrogen absorption of legume. Centrosema pubescens (Centro) and Pueraria phaseoloides (Puero), soil from Tenbalang, manure, an organic fertilizer ( N,P,K and KI ). H2SO4 solution, aquades, HCL, NaOH, indikator MR+MB, and blanko solution. The experiment also used 24 pot for plantation with 10 kg capacity , analytic balance etc. The experiment used 4 x 2 factorial completely randomized design. The first factor were Centro (Centrosema pubescens)- (L1) and Puero (Pueraria phaseoloides)- (L2) and the level of iodine fertilizer (I0) without iodine, I1 (iodine 5 kg/ha), I2 (iodine 10 kg/ha) and I3 (iodine 15 kg/ha) were the second factor. Application of iodine fertilizer has no significant result, to nitrogen absorption, nitrat reductase activity, crude protein contain, and fibre. In the other hand, the interaction between legume and iodine has significantly result on the efficient and absorption of nitrogen, crude protein. The conclusion showed that puero was more responsive than centro, however centro was more potential in efficiency and absorption of N and crude protein.